2019
DOI: 10.4236/me.2019.109136
|View full text |Cite
|
Sign up to set email alerts
|

Causal Relationships between Energy Consumption, Economic Growth and CO<sub>2</sub> Emission in Sub-Saharan: Evidence from Dynamic Simultaneous-Equations Models

Abstract: The purpose of this study is to investigate the interrelationship between energy-CO 2 emission-GDP for Sub-Saharan countries covering the period 2000-2012. To circumvent this issue we use dynamic simultaneous-equation. Our empirical findings show that there is a bidirectional causal relationship between energy consumption and economic growth. The results support also a bidirectional relationship between energy consumption and electricity consumption, but variables reflecting pollution affect negatively electri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 79 publications
0
8
0
Order By: Relevance
“…We agree with Barrassi & Spagnolo (2012) that such an imposition is too restrictive. Also, several studies (including Acheampong, 2018;Barassi & Spagnolo, 2012;Zaidi & Ferhi, 2019) have confirmed that bi-directional causality exist between the two. Accordingly, we capture the possibility of reverse causality as follows:…”
Section: Empirical Model Data and Methodologymentioning
confidence: 92%
See 1 more Smart Citation
“…We agree with Barrassi & Spagnolo (2012) that such an imposition is too restrictive. Also, several studies (including Acheampong, 2018;Barassi & Spagnolo, 2012;Zaidi & Ferhi, 2019) have confirmed that bi-directional causality exist between the two. Accordingly, we capture the possibility of reverse causality as follows:…”
Section: Empirical Model Data and Methodologymentioning
confidence: 92%
“…The EKC has generated a plethora of empirical examinations, with some (Fang et al, 2018;Kasperowicz, 2015;Lu, 2017;Zou & Zhang, 2020) confirming it while others (Aye & Edoja, 2017;Munir & Khan, 2014;Omotor, 2016) reject it. Several studies (Odhiambo, 2017;Omri et al, 2015;Spagnolo, 2012;Zaidi & Ferhi, 2019) have considered testing for causality between the variables.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Gövdeli (2019) identifies causality from income to environmental pollution in 26 OECD countries and Stamatiou and Dritsakis (2019) determine unidirectional causality from income to environmental pollution in Italy. The tests performed by Zaidi and Ferhi (2019) show a bidirectional linear association between income and the environment in sub-Saharan countries. demonstrate that in the case of BRICS countries, there is a positive interaction between income and the environment.…”
Section: Literature Reviewmentioning
confidence: 96%
“…Because natural resources are related to environmental degradation, increasing natural resource extraction and unsustainable consumption increase CO2 emissions in Bangladesh (Zaidi and Ferhi 2019).…”
Section: Estimating Nardl Modelmentioning
confidence: 99%